Targeted protein degradation: Emerging concepts and protein state-specific targeting principles. (April 2022) - Tao, Andrew J.; Gadbois, Gillian E.; Buczynski, Stanley A.; Ferguson, Fleur M.
Abstract: Targeted protein degraders are heterobifunctional small molecules that link a target ligand or bait to an E3-ligase binder via a chemical spacer. Upon entering the cell, these ligands trigger the formation of a ternary complex between the target protein, degrader and E3-ligase, which leads to target polyubiquitination and proteasomal degradation. In recent years, TPD has expanded rapidly as a field, becoming the modality of choice in drug discovery and chemical probe development. This has been driven by the unique pharmacology of these molecules, which allows for fast and reversible knockdown of the target protein. Recent studies have demonstrated that degraders with specificity for a defined subpopulation of a protein-of-interest can be developed, giving rise to the emerging concept of protein state-specific targeting. In this article, we review advances towards developing degraders that differentiate between target protein subpopulations based on their; activation state, oligomerization state, cellular localization state, and cell type.